Black American Agricultural Experts and the Vernacularization of American Science in Liberia Prior to Decolonization in Africa - Mark-Thiesen, Cassandra (Journal of West African History, 2024)
Studies continue to assume an unbridgeable gap between scientific representations and ontological realities in Africa. Histories of foreign scientific interventions on the continent have often emphasized the role of scientists as agents of empire. However, there is a growing body of historiography that explores how adaptation and translation took place against the backdrop of the massive power imbalances that characterized such knowledge transfers, including in relation to the complex and shifting positions of the scientists themselves. This article focuses on black American agricultural scientists who advised the Liberian government on how to grow surplus crops nationally. It examines their practice of linking science to local knowledge. It also explores their personal negotiations with American empire as they infused their work with black internationalist theories of liberation and racial uplift. By looking at scientists on the ground or in the field, we can learn more about embedded processes of epistemic and political negotiation and critique.
Keywords: Science; transfer; black internationalism; rural; Africa; Liberia; United States; Tuskegee